Indications for surgical treatment of stomach ulcer - Suiffet, Walter; Sojo, Enrique (Cirugía del Uruguay, 1978)
The paper contains an analysis of indications for surgical treatment of G. U. based on current knowledge on the subject. The study on a more realistic basis of ulcerated stomach lesions has led to a better classification of clinical cases, with respect to diagnosis of bening and malign lesions. Radiology, endoscopy, citology and biopsy reach a leve! of exactness which may be as high as 99.4 % in the best statistics. It is on this basis that the surgical indications for the different lesiona! stages of G. U. are set forth. There is still one problem in attaining certainty of diagnosis and that is the biological cycle of malign ulcers and the possibility of bening lesions becoming malign. The analysis of medical and surgical indications should be accompanied by a prospective study of modern methods of diagnosis.